Beyond Mooting: Designing an Advocacy, Ethics and Values Matrix for the Law School Curriculum - Bobette Wolski (Legal Education Review)
Improving students’ computer literacy, instilling a critical approach to Internet resources and preparing them for collaborative work are important educational aims today. This article examines how a writing exercise in the style of a Wikipedia article can be used to develop these skills. Students in an elective unit in Comparative Law were asked to create, and review, a Wikipedia entry on an issue, concept or scholar in this field. This article describes the rationale for adopting this writing task, how it was integrated into the teaching and assessment structure of the unit, and how students responded to the exercise. In addition to critically evaluating the potential of this novel teaching tool, the article aims to provide some practical guidance on when Wikipedia assignments might be usefully employed.